Designing a Metacognitive Training Mobile Application and Evaluating Its Effectiveness on Meta-Worry and Metacognitive Beliefs in University Students with Anxiety Symptoms - Ebrahimi, Seyedeh Somayeh; Ghorban Jahromi, Reza; Karimzadeh, Mansoureh; Shahabi, Seyed Rouhollah (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to design a metacognitive training mobile application and to determine its effectiveness in reducing meta-worry and improving metacognitive beliefs among university students with anxiety symptoms. Methods and Materials: This study employed a mixed-methods (qualitative–quantitative) design. In the qualitative phase, the content validity of the developed application was evaluated by five experts using the Content Validity Ratio (CVR) and Content Validity Index (CVI), and the application was piloted with a small number of participants prior to the main implementation. In the quantitative phase, a quasi-experimental pretest–posttest design with a control group was used. The population comprised university students diagnosed with anxiety symptoms in universities in Tehran, and 30 students were selected via convenience sampling and randomly assigned to equal experimental and control groups. Data were collected using the Meta-Worry Questionnaire (Wells, 2006) and the Metacognitions Questionnaire (Wells & Cartwright-Hatton, 2004). The experimental group received the metacognitive training application (including instructional content and practice sessions), whereas the control group received no intervention. Content validity indices indicated acceptable validity (CVR = 1.00; CVI > 0.79). Findings: Descriptive statistics were first reported, and assumptions for univariate and multivariate ANCOVA were examined. Hypothesis testing showed that the metacognitive training application significantly reduced meta-worry (F= 5.24, p<.05) and improved metacognitive beliefs (F = 38.97, p< .01). Conclusion: The findings suggest that metacognitive processes—particularly meta-worry and negative metacognitive beliefs—play a key role in maintaining and exacerbating anxiety, and that app-based metacognitive training can be used as an accessible and effective intervention.